β-Adrenergic signaling, monoamine oxidase A and antioxidant defence in the myocardium of SHR and SHR-mtBN conplastic rat strains: the effect of chronic hypoxia - Hahnova, Klara; Brabcova, Iveta; Neckar, Jan; Weissova, Romana; Svatonova, Anna; Novakova, Olga; Zurmanova, Jitka; Kalous, Martin; Silhavy, Jan; Pravenec, Michal; Kolar, Frantisek; Novotny, Jiri (The journal of physiological sciences, 2018)
The β-adrenergic signaling pathways and antioxidant defence mechanisms play important roles in maintaining proper heart function. Here, we examined the effect of chronic normobaric hypoxia (CNH, 10% O2, 3 weeks) on myocardial β-adrenergic signaling and selected components of the antioxidant system in spontaneously hypertensive rats (SHR) and in a conplastic SHR-mtBN strain characterized by the selective replacement of the mitochondrial genome of SHR with that of the more ischemia-resistant Brown Norway strain. Our investigations revealed some intriguing differences between the two strains at the level of β-adrenergic receptors (β-ARs), activity of adenylyl cyclase (AC) and monoamine oxidase A (MAO-A), as well as distinct changes after CNH exposure. The β2-AR/β1-AR ratio was significantly higher in SHR-mtBN than in SHR, apparently due to increased expression of β2-ARs. Adaptation to hypoxia elevated β2-ARs in SHR and decreased the total number of β-ARs in SHR-mtBN. In parallel, the ability of isoprenaline to stimulate AC activity was found to be higher in SHR-mtBN than that in SHR. Interestingly, the activity of MAO-A was notably lower in SHR-mtBN than in SHR, and it was markedly elevated in both strains after exposure to hypoxia. In addition to that, CNH markedly enhanced the expression of catalase and aldehyde dehydrogenase-2 in both strains, and decreased the expression of Cu/Zn superoxide dismutase in SHR. Adaptation to CNH intensified oxidative stress to a similar extent in both strains and elevated the IL-10/TNF-α ratio in SHR-mtBN only. These data indicate that alterations in the mitochondrial genome can result in peculiar changes in myocardial β-adrenergic signaling, MAO-A activity and antioxidant defence and may, thus, affect the adaptive responses to hypoxia.
Keywords: adenylátcyklasy; signální transdukce; Signal Transduction; monoaminoxidasa; Malondialdehyde; beta-adrenergní receptory; krysa rodu Rattus; Monoamine Oxidase; Adenylyl Cyclases; Hypoxia; zvířata; Monoamine oxidase A; Chronic hypoxia; Antioxidant defence; hypoxie; Mitochondrial genome; Receptors, Adrenergic, beta; Male; potkani inbrední SHR; β-adrenergic receptors; Rats; myokard; Animals; Myocardium; mužské pohlaví; SHR; Rats, Inbred SHR; malondialdehyd; Adenylyl cyclase